2023
DOI: 10.1155/2023/6479187
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Development of Health Digital GIS Map for Tuberculosis Disease Distribution Analysis in Sudan

Abstract: Health digital GIS map provides a great solution for medical geographical distribution to efficiently explore diseases and health services. In Sudan, tuberculosis disease is expanding in different areas, which requires a digital GIS map to collect information about the patients and support medical institutions by geographical distribution based on health services, drug supply, and consumption. This paper developed a health digital GIS map to provide a fair geographical distribution of tuberculosis health cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…We analyzed the prevalence of ODs and SSDs in children across different administrative districts and geographical zones in the Odesa region, using local GIS data. The study supported the experts' view on the usefulness of GIS as a tool for collecting, storing, analyzing, and visualizing geographic data and related medical information [9][10][11]. The results showed that the "null hypothesis" of a uniform distribution of GHD, CF, ALL and T1DM cases in children throughout the Odesa region was not confirmed.…”
Section: Discussionsupporting
confidence: 53%
“…We analyzed the prevalence of ODs and SSDs in children across different administrative districts and geographical zones in the Odesa region, using local GIS data. The study supported the experts' view on the usefulness of GIS as a tool for collecting, storing, analyzing, and visualizing geographic data and related medical information [9][10][11]. The results showed that the "null hypothesis" of a uniform distribution of GHD, CF, ALL and T1DM cases in children throughout the Odesa region was not confirmed.…”
Section: Discussionsupporting
confidence: 53%
“…The recognition of epidemics holds great importance in public health, and understanding the geographical distribution of a disease is one of the most effective factors in this process. Since disease prevalence is related to the environment and climate, studying geographical conditions becomes essential [ 16 , 17 ]. However, spatial data analysis for investigating epidemics often presents challenges, prompting public health experts to seek solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%